2018
DOI: 10.5811/westjem.2018.3.37076
|View full text |Cite
|
Sign up to set email alerts
|

Transaminase and Creatine Kinase Ratios for Differentiating Delayed Acetaminophen Overdose from Rhabdomyolysis

Abstract: IntroductionRhabdomyolysis and delayed acetaminophen hepatotoxicity may be associated with elevated serum transaminase values. Establishing the cause of elevated transaminases may be especially difficult because of limited or inaccurate histories of acetaminophen ingestion. We hypothesized that the comparative ratios of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and creatine kinase (CK) can differentiate acetaminophen hepatotoxicity from rhabdomyolysis.MethodsA retrospective chart review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…[27] Secondly, PM/DM is characterized by autoimmune conditions that target muscles to some degrees [28], and elevated serum CK, AST, ALT levels have been associated with increased levels of injury to skeletal muscle. [27,29] The positive association of CK with the DRR in our cohort provides support for this mechanism. What's more, pulmonary infection, mainly bacterial, is the most common cause of acute exacerbation in patients with ILD.…”
Section: Discussionsupporting
confidence: 63%
“…[27] Secondly, PM/DM is characterized by autoimmune conditions that target muscles to some degrees [28], and elevated serum CK, AST, ALT levels have been associated with increased levels of injury to skeletal muscle. [27,29] The positive association of CK with the DRR in our cohort provides support for this mechanism. What's more, pulmonary infection, mainly bacterial, is the most common cause of acute exacerbation in patients with ILD.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that a CK/AST and CK/ALT ratio lower than the cutoff point of 15–20 is helpful in diagnosing concurrent hepatic injury in rhabdomyolysis. The ratio of CK/AST (11.7) and CK/ALT (14.9) in this patient was less than 15, pointing to the presence of acute liver injury ( 18 ). The R value (the ratio of ALT to alkaline phosphatase) was 9.8, suggestive of predominant hepatocellular rather than cholestatic hepatitis.…”
Section: Discussionmentioning
confidence: 68%
“…First, prolonged hypoxemia, caused by exacerbation of diffusing capacity for carbon monoxide (DLco), that is further increased with the development of ILD may result in increased pulmonary artery pressures, leading to increased right ventricle afterload, which promotes hepatocyte injury and AST level increased more [ 27 ]. Secondly, PM/DM is characterized by autoimmune conditions that target muscles to some degrees [ 28 ], and elevated serum CK, AST, and ALT levels have been associated with increased levels of injury to the skeletal muscle [ 27 , 29 ]. The positive association of CK with the DRR in our cohort provides support for this mechanism.…”
Section: Discussionmentioning
confidence: 99%